Synthesis and photoelectric performances of blue-green emitting iridium phenylpyridine complexes using N, N′-heteroaromatic ancillary ligands. (11th May 2015) - Huixia, Xu; Peng, Sun; Dan, Zhao; Tingting, Yang; Yuying, Hao; Hua, Wang; Heping, Shi; Bingshe, Xu
Abstract : Four (ppy)2 Ir(N ∧ N) complexes were synthesized and the effects of their molecular structures on photoelectric performances were investigated in detail. Abstract : Four iridium complexes containing different ancillary ligands Htfmpptz = 2-(5-(4-(trifluoromethyl)phenyl)-2 H -1, 2, 4-triazol-3-yl)pyridine, Hfpptz = 2-(5-(4-fluorophenyl)-2 H -1, 2, 4-triazol-3-yl)pyridine and Htfmptz = 2-(5-(trifluoromethyl)-2 H -1, 2, 4-triazol-3-yl)pyridine and ppy (2-phenylpyridine) as main ligands were synthesized and characterized. Their molecular structures were identified by X-ray single crystal diffraction. The effects of ancillary ligands on the photophysical and luminescence behaviors were investigated. The emission maximum peaks of (ppy)2 Ir(tfmpptz), (ppy)2 Ir(fpptz) and (ppy)2 Ir(tfmptz) in CH2 Cl2 solution appear at 485, 487 and 483 nm, respectively. Phosphorescent organic light-emitting devices (PhOLEDs) were fabricated using these complexes doped in CBP as an emitting layer.